Beans (Phaseolus spp.)- model food legumes - Broughton, W.J.; Hernández, G.; Blair, Matthew W.; Beebe, Stephen E.; Gepts, Paul L.; Vanderleyden, J (2003)
Globally, 800 million people are malnourished. Heavily subsidised farmers in rich countries produce sufficient surplus food to feed the hungry, but not at a price the poor can afford. Even donating the rich world’s surplus to the poor would not solve the problem. Most poor people earn their living from agriculture, so a deluge of free food would destroy their livelihoods. Thus, the only answer to world hunger is to safeguard and improve the productivity of farmers in poor countries. Diets of subsistence level farmers in Africa and Latin America often contain sufficient carbohydrates (through cassava, corn/maize, rice, wheat, etc.), but are poor in proteins. Dietary proteins can take the form of scarce animal products (eggs, milk, meat, etc.), but are usually derived from legumes (plants of the bean and pea family). Legumes are vital in agriculture as they form associations with bacteria that ‘fix-nitrogen’ from the air. Effectively this amounts to internal fertilisation and is the main reason that legumes are richer in proteins than all other plants. Thousands of legume species exist but more common beans (Phaseolus vulgaris L.) are eaten than any other. In some countries such as Mexico and Brazil, beans are the primary source of protein in human diets. As half the grain legumes consumed worldwide are common beans, they represent the species of choice for the study of grain legume nutrition. Unfortunately, the yields of common beans are low even by the standards of legumes, and the quality of their seed proteins is sub-optimal. Most probably this results from millennia of selection for stable rather than high yield, and as such, is a problem that can be redressed by modern genetic techniques. We have formed an international consortium called ‘Phaseomics’ to establish the necessary framework of knowledge and materials that will result in disease-resistant, stress-tolerant, high-quality protein and high-yielding beans. Phaseomics will be instrumental in improving living conditions in deprived regions of Africa and the Americas. It will contribute to social equity and sustainable development and enhance inter- and intra-cultural understanding, knowledge and relationships. A major goal of Phaseomics is to generate new common bean varieties that are not only suitable for but also desired by the local farmer and consumer communities. Therefore, the socio-economic dimension of improved bean production and the analysis of factors influencing the acceptance of novel varieties will be an integral part of the proposed research (see Figure 1). Here, we give an overview of the economic and nutritional importance of common beans as a food crop. Priorities and targets of current breeding programmes are outlined, along with ongoing efforts in genomics. Recommendations for an international coordinated effort to join knowledge, facilities and expertise in a variety of scientific undertakings that will contribute to the overall goal of better beans are given. To be rapid and effective, plant breeding programmes (i.e., those that involve crossing two different ‘parents’) rely heavily on molecular ‘markers’. These genetic landmarks are used to position important genes (e.g. for resistance to particular pests, for yield, etc.) on a chromosome and ensure that they can be ‘crossed in’ to another plant. There are several ways of obtaining molecular markers but the project will establish partial sequences of messenger RNA’s extracted from tissues of interest (e.g. developing pods). These so-called expressed sequence-tags (ESTs), can be used like milestones on a chromosome, to position these and other genes. These efforts will complement current studies on other legumes such as Lotus japonicus and Medicago truncatula as well as the EST projects in soybean by providing a framework for comparative genomics between legumes. Complete sequencing and molecular analysis of the bean genome will follow. Individual laboratories will be encouraged to internally finance or find additional funding for the construction of cDNA libraries and the sequencing of thousands ESTs. Funds donated to the consortium will be used primarily for sequencing the genome and to co-ordinate the consortium’s activities. As sequence and expression data become available it will provide an elaborate framework for plant geneticists to ‘design’ new, improved common bean lines. Amongst these lines will be higher-yielding varieties, cultivars that are resistant to drought, pests and so on. It will also be possible to enhance the content of essential amino acids, minerals and vitamins in the seeds and so improve the nutrition and health of countless people who consume beans. By considering the socio-economic implications of common bean improvement from the outset, this project should lead to sustainable development, to increased social equity, and to greater use of beans in international trade. The added value in this innovative approach to common beans as model food legumes lies in the combination of existing and novel genetic approaches with socio-economic criteria that will efficiently target the end users.